A New Precise Color Sense Anomaly Test - TSUTSUMI, Shuichi (Japanese Journal of National Medical Services, 1970)
This color sense anomaly test can investigate precisely the intensity, form and locality of the color sense anomaly, in the whole color sense space. This test can determine precisely the color sense anomaly grade, form and inclination.